Anxiety, depressive symptoms, and quality of life in mothers of newborns with congenital malformations: a follow-up study during the first year after birth (Research, Society and Development, 2021)
Objective: To evaluate the quality of life, anxiety, and depressive symptoms of mothers of newborns with congenital malformations admitted to the neonatal intensive care unit (NICU) and followed up during their first year of life. Methods: Longitudinal study carried out with mothers who had newborns with structural congenital malformations admitted to the NICU. Three outcomes were evaluated: (1) quality of life using the WHOQoL-BREF, (2) anxiety using the State-Trait Anxiety Inventory, and (3) depressive symptoms using the Beck Depression Inventory. Five evaluations were carried out: between 24h and 48h after the newborn's hospitalization, upon discharge from the NICU, three, six, and 12 months of life. Longitudinal changes in the scores of the outcomes of interest were analyzed using the Friedman test with post-hoc Conover assessment for multiple comparisons. Results: Sixteen mothers were followed for one year. During the follow-up period, no significant changes were observed in the quality of life scores, with the exception of the psychological domain (p = 0.023), especially when comparing admission to the NICU with values obtained 12 months after the child's birth (p = 0.006). Increased scores of trait-anxiety and state-anxiety were observed at 6 months of life in relation to the first assessment, being classified as severe in 75.0% and 87.5% of the mothers, respectively. Conclusion: Mothers of children with congenital malformations showed important changes in their psychological state. It is necessary to implement psychosocial support programs that promote the investigation and treatment of maternal mental disorders, especially during the first six months of the child's life.